Temperature‐Responsive Ultrasonic‐Wave Engineering Using Thermoresponsive Polymers. (29th July 2021) - Lee, Sang Jun; Lee, Haunmin; Lim, Dahyun Daniel; Song, Chanho; Choi, Wonjoon
Abstract: Artificial structures for controlling ultrasonic‐waves are attractive for developing superb functions in sensing‐imaging techniques. However, the complicated fabrication and fixed design associated with the particular wave limit the scalability. Herein, a versatile‐reversible ultrasonic‐wave engineering using programmable heating of local areas on thermoresponsive polymers is presented. As an abrupt shift of the elastic modulus occurs at selectively heated zones over the glass transition temperature, the drastic modulus change alters the S0 phase velocity of the Lamb wave within ultrasonic waves passing through the heated regimes. The modified wave propagation results in an active wavelength shift and wave refraction, which enables multifunctional programming of wave propagation pathways and wavefront shapes. Multiple functions such as reduced wavelength, wave steering, energy focusing and bifurcation are implemented in one nylon 6 thermoresponsive polymer, according to predesigned heating shapes. This work demonstrates the capability of temperature‐responsive wave engineering in bulk solid media with only a heating configuration. Abstract : Programmable heating of local areas on thermoresponsive polymers offers versatile‐reversible ultrasonic‐wave engineering. The drastic modulus change at the glass transition temperature activated by selective heating configuration inside the media conducts a pre‐designed wavelength shift and wave refraction, which enable multiple functions, such as reduced wavelength, wave steering, energy focusing, and bifurcation.